Revisiting Open Science Through a Global Health Lens: Critical Reflections - Caravaca-Morera, Jaime Alonso (2025)
Open Science has become a global movement promoting accessibility, transparency, and collaboration in research. It encompasses open access, open data, citizen science, and digital innovations, fostering inclusion and public participation, particularly in social and health sciences. This shift challenges traditional scientific models by emphasizing ethical integrity, research transparency, and knowledge co-creation. However, issues like authorship, funding, and scientific misconduct remain critical concerns. Open Science enhances research efficiency, democratizes knowledge, and strengthens institutional impact. This article aims to map current and future Open Science initiatives in global health, providing a systematic framework to support decision-making and scientific adaptation to this evolving landscape.